(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article scientifically analyses the socio-psychological model of family relations, typology, structure, forms of family, methods of upbringing, as well as issues of modern family problems. In addition to psychological literature, the article used pedagogical literature.